Perspectives on immigration and terrorism - Ruggiero, Giovanni Maria (NATO science for peace and security series. E, Human and societal dynamics, 2011)
Globalization, accompanied by more options for communication, has led to sweeping changes which mean that the economic, political and cultural realities of one country may influence those of other countries, despite them being geographically far apart. Increased migration, both within and across national borders, serves only to amplify the potential problems that this can cause. Trauma and violence are often associated with the migration process, and even where they are not, migration and immigration represent a massive challenge to individuals which frequently involves loss of identity, alienation and discrimination. This book is a collection of 16 papers from the NATO sponsored meeting entitled Perspectives on Immigration and Terrorism, which took place in Milan (Italy) in March 2010, and which focused on the psychological and socio-cultural precursors to the radicalization of immigrant youth in Europe. Some of the topics explored include: factors of cultural and ideological opposition to western societies; the growing pressure of the process of secularization; illegal aspects of terrorism; immigration as a possible trajectory for political radicalism; the interaction between traumatic experience and immigration; acculturation and adjustment to a new culture; potential predictors of terrorist behavior and the role of a sense of national belonging. The book provides many perspectives on the way in which vulnerability to radical ideology may develop among individuals whose lack of personal and social resources may result in alienation, frustration and desperation. It also offers solutions which might be implemented to mitigate or prevent this problem.